Log in to add a comment

## Answers

ax² + bx - 6 = 0

ax² + bx = 6

x(ax + b) = 6

ax + b = 6/x

3a/4 + b = 6 / (3/4)

3a/4 + b = (6 * 4) / 3

3a/4 + b = 24/3

3a/4 + b - 8 = 0 ---------------1

b = 8 - 3a/4

Now

Let x = -2

a(-2)² + b * -2 - 6 = 0

4a - 2b -6 = 0

4a - 2b = 6 --------------2

So,

4a = 6 + 2b

a = (6 + 2b)/4

Substituting the value of a in equation 1

3a/4 + b - 8=0

3(6 + 2b) / 16 + b = 8 taking LCM

(18 + 6b + 16b)/16 = 8

18 + 22b = 8 * 16

22b = 128 - 18

22b = 110

**b = 110/22 = 5**

Substituting The Value Of b in Equation 2

4a - 2b = 6

4a - 2*5 = 6

4a - 10 = 6

4a = 6 + 10

4a = 16

**a = 16/4 = 4**

**Therefore the values of a and b are 4 and 5 respectively**